1988
DOI: 10.1159/000293668
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Adrenal Involution during Antenatal and Neonatal Periods

Abstract: Using real-time ultrasonography, 25 adrenal glands from prenatal to neonatal periods were prospectively examined to assess the process of shrinkage. A similar sonographic structure was seen in both prenatal and neonatal adrenal glands. The area of adrenal gland (AGA) and the rate of decrease were calculated during antenatal and early neonatal periods. The values of AGA were 350 ± 19 mm2 within a week of delivery, 304 ± 17 mm2 (87 ± 2%) just after delivery, 273 ± 25 mm2 (77 ± 5%) on the 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Moreover, the same pattern has also been described for plasma and urinary DHEA-S levels in preterm and full-term infants (28,29); and in the same line higher DHEA-S levels were reported for extremely preterm infants (23-26 weeks gestation) compared to very preterms (27-29 weeks gestation) in the first week of life (30). Morphometric studies using prenatal and neonatal ultrasound imaging or autopsy methods revealed that the fetal adrenals shrink faster in full-term compared to preterm infants (31,32). On the other hand, a study including infants of 26-35 weeks gestation suggested that parturition is the trigger for the involution of the fetal adrenals (33).…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the same pattern has also been described for plasma and urinary DHEA-S levels in preterm and full-term infants (28,29); and in the same line higher DHEA-S levels were reported for extremely preterm infants (23-26 weeks gestation) compared to very preterms (27-29 weeks gestation) in the first week of life (30). Morphometric studies using prenatal and neonatal ultrasound imaging or autopsy methods revealed that the fetal adrenals shrink faster in full-term compared to preterm infants (31,32). On the other hand, a study including infants of 26-35 weeks gestation suggested that parturition is the trigger for the involution of the fetal adrenals (33).…”
Section: Discussionsupporting
confidence: 58%
“…A decline in steroid secretion at birth is also well documented (1, 8 -11). It was suggested that in full-term infants the adrenal gland involutes more rapidly (13,14). Results of this study show that within the first 2 wk of life, the large fetal adrenal shrinks to its normal infantile size.…”
Section: Discussionmentioning
confidence: 99%